2014
DOI: 10.1586/1744666x.2015.992881
|View full text |Cite
|
Sign up to set email alerts
|

Clinical management of multiple sclerosis and neuromyelitis optica with therapeutic monoclonal antibodies: approved therapies and emerging candidates

Abstract: Therapeutic monoclonal antibodies (mAbs) are a relatively novel class of drugs that has substantially advanced immunotherapy for patients with multiple sclerosis. The advantage of these agents is that they bind specifically and exclusively to predetermined proteins or cells. Natalizumab was the first mAb in neurology to obtain approval. It is also considered one of the most potent options for annualized relapse rate reduction among available therapeutic options. Alemtuzumab is currently also approved in severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 100 publications
0
21
0
Order By: Relevance
“…In addition, clinically, AxD, especially type 2, shows stepwise or stroke-like progression, which is similar to the typical progression of other white matter diseases involving oligodendrocytes, MS and NMO. These findings suggest that the neuroinflammatory process promoted by proinflammatory astrocytes may be involved in the pathogenesis of AxD, and that immunomodulation approaches [33] targeting astrocytopathy would be a candidate therapy for AxD. Recent studies showed that astrocytes themselves can secrete cytokines and have responsibility for extrinsic factors, including LPS [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, clinically, AxD, especially type 2, shows stepwise or stroke-like progression, which is similar to the typical progression of other white matter diseases involving oligodendrocytes, MS and NMO. These findings suggest that the neuroinflammatory process promoted by proinflammatory astrocytes may be involved in the pathogenesis of AxD, and that immunomodulation approaches [33] targeting astrocytopathy would be a candidate therapy for AxD. Recent studies showed that astrocytes themselves can secrete cytokines and have responsibility for extrinsic factors, including LPS [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Rituximab is a chimeric mouse–human IgG1k mAb that binds to the CD20 cell surface epitope on circulating B‐cells (Reff et al , ). It lyses peripheral B‐cell populations through a threefold mechanism of action: a combination of ADCC and CDC and possibly promotion of apoptosis (Dubey et al , ). Rituximab is approved for patients with non‐Hodgkin's lymphoma, chronic lymphocytic leukaemia, rheumatoid arthritis, granulomatous polyangiitis and microscopic polyangiitis (Gasperi et al , ).…”
Section: Mab Therapies For Relapsing Ms: Efficacy and Mechanisms Of Amentioning
confidence: 99%
“…Anti-CTLA-4 treatment increased clinical signs of EAE in animal models [145,146]. Abatacept has showed safety and favorable immunological effects in a phase I clinical trial in patients with RRMS [147], while an initial placebo-controlled phase II trial in 219 patients was halted prematurely because of an increased relapse rate and MRI activity in an abatacepttreated group [148]. However, a post-hoc analysis revealed that patients in this treatment arm had a higher baseline activity at the time of study inclusion, providing the rationale for another attempt a few years later.…”
Section: Anti-ctla-4-directed Therapy (Abatacept)mentioning
confidence: 99%